Peran Serta Masyarakat dalam Penyusunan RDTR Wilayah Perencanaan Selatan Kota Denpasar - Lestari, Eka; Pandawani, Ni Putu; Partama, I GD. Yudha; Widnyana, I Ketut (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2024)
This research aims to develop a strategy to increase community participation in instigating a Detailed Spatial Plan (RDTR) for the Southern Region of Kota Denpasar to minimize deviations during its implementation. This research used a mixed method, preceded by a qualitative data collection, and then progressed to a quantitative data collection. Distribution of questionnaires aided both started in January and ended in May 2024. Three forms of analysis are used: qualitative descriptive analysis, interval analysis, and SWOT. Study findings show that the stage of community participation falls into the category of consultation level - the fourth step on Arnstein's participation ladder. This is included in the degree of tokenism category. Based on the internal-external (IE) matrix analysis results in SWOT, the position of community participation is in cell II. The appropriate strategy to be used is the growth and development strategy. At this stage, the required actions are either intensive (information, dissemination, strengthening regulations, and innovation) or integrative (controlling information, strengthening human resource capacity, and cooperation/partnership). This research also leads to a range of opportunities to conduct further studies discussing community participation in policy conformance, land utilization control, and the application of e-participation and partnership. Keywords: participation; spatial planning[ RDTR; level of participation; Internal-External (IE) matrix   Abstrak Penelitian ini bertujuan untuk menyusun strategi peningkatan peran serta masyarakat di dalam tahap penyusunan Rencana Detail Tata Ruang (RDTR) Wilayah Perencanaan (WP) Selatan Kota Denpasar, dalam rangka meminimalisir terjadinya simpangan saat implementasi. Penelitian ini menggunakan metode campuran (mixed method) yang diawali dengan pengumpulan data kualitatif, dan kemudian dilanjutkan dengan perolehan data kuantitatif. Proses pengumpulan data dibantu oleh penyebaran kuesioner yang dimulai di bulan Januari dan berakhir di bulan Mei 2024. Ada tiga frame analisis yang diterapkan, yaitu analisis deskriptif kualitatif, analisis interval dan SWOT. Hasil penelitian menunjukkan bahwa tingkat partisipasi masyarakat berada pada level consultation yaitu tangga keempat dari tingkatan partisipasi Arnstein yang masuk dalam kategori degree of tokenism . Berdasarkan hasil analisis matrik internal-eksternal (IE) dalam SWOT, posisi peran serta masyarakat berada di sel II dimana strategi yang tepat digunakan yaitu strategi tumbuh dan membangun. Di dalam tahapan ini, aksi yang disyaratkan yaitu bersifat intensif  (penyebarluasan informasi, penguatan regulasi, dan inovasi) atau integratif (memegang kendali informasi, penguatan kapasitas SDM, dan kerjasama/ partnership ). Penelitian ini juga membuka peluang untuk beberapa studi lanjutan yang mendalami peran serta masyarakat pada tahap pentaatan kebijakan, pengendalian pemanfaatan ruang serta penerapan e-participation dan partnership . Kata kunci: peran serta masyarakat; tata ruang; RDTR, tingkat partisipasi; matrik Internal-Eksternal (IE)